Letramento e categorização semântica - Plantin, Rosemeire Selma Monteiro (2019)
Investigation about the influence of the literacy and schooling in the semantic memory structure, more specifically about categorization capacity. The first aim for this work were to see differences between literates and illiterate’s structure of semantic memory. For this, in a Pschycolinguistic and the Cognitive Psychology perspective there are applied a experimental test in 43 subjects with difference schoolarization’s levels. The implications principals founded in this search are which the categorizations of the illiterates are based in the functionless and/ our perceptives propriety.